Pelatihan Inovasi Produk Ramah Lingkungan untuk Meningkatkan Daya Saing UMKM di Kawasan Wisata Taman Bunga Okura - Mariaty Ibrahim; Etika Etika; Elti Martina; M. Zacky Faluti; Nurul Asyifa; Yogi Prambudi (Civiliza Publishing, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting community economic growth and enhancing the competitiveness of tourism destinations through the provision of products and services that meet tourists' needs. However, many MSME actors in tourism areas still face limitations in developing innovative products based on environmental sustainability principles. This community service program aimed to enhance the capacity of MSME actors in developing environmentally friendly products through product innovation training conducted in the Taman Bunga Okura Tourism Area, Pekanbaru. The program was implemented using a community education approach in the form of educational seminars, focus group discussions (FGDs), and participatory approaches through direct training for MSME participants. The activities included needs assessment, preparation of training materials, presentation of eco-friendly product concepts, interactive discussions, case studies, and simulations of product development based on local resources. The results indicated an improvement in participants' understanding of sustainable business concepts, the utilization of environmentally friendly materials, and awareness of market opportunities for green products in the tourism sector. Furthermore, participants gained a better understanding of the importance of packaging innovation, waste reduction, and the optimization of local potential as strategies for enhancing business competitiveness. This program is expected to contribute to strengthening tourism-based MSMEs and promoting more environmentally sustainable local economic development.